SISTEM INFORMASI RENTAL SEPEDA MOTOR BERBASIS PHP : Hypertext Prepocessor: SISTEM INFORMASI RENTAL SEPEDA MOTOR BERBASIS PHP : Hypertext Prepocessor - Prakarsya, Agustian; Megira, Selvy; M.Pd, Firdaus , (Universitas Lembah Dempo, 2022)
The application of computer technology-based information systems in the business world has now become a very urgent necessity, this is one of the competitive advantage strategies. The information system is one of the right choices to optimize productivity. With the use of computers and mastery of skills in using integrated software, the data processing process will be carried out easily, quickly and accurately. A result of developing an information system must support organizational activities for a certain period of time, because the existence of an information system will be adapted to the development of the organization or company. The complexity of the company that is driven by very dynamic environmental changes needs to be supported by the existence of a new design that can support the increasing information needs of system users in order to keep the company ahead of competitors and keep in tune with the technological revolution and its impact on the product or service. company services. Motorcycle rental is one of the business fields that manages entertainment facilities in the form of vehicle rental services. With the increasing number of consumers who need motorbike loan services, more and more problems arise in providing services to consumers. Because the service system provided by the management is mostly done manually, of course this method is not efficient both in terms of energy and time..